2022
DOI: 10.4014/jmb.2112.12056
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 Inhibits Trophoblast Proliferation, Migration, and EMT via Activating p38 MAPK Signaling Pathway to Promote Recurrent Spontaneous Abortion

Abstract: Recurrent spontaneous abortion (RSA), defined as the loss of ≥2 consecutive pregnancies before the 24th gestational week, affects 1%-2% women during their reproductive age [1]. As a common condition in reproductive medicine, RSA is reported in 1-2% of fertile couples seeking pregnancy and inflicts a significant physical, emotional, and financial burden on many families [2]. Many factors are thought to contribute to RSA, such as parental chromosomal abnormalities, maternal thrombophilia, immune dysfunction, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The following KEGG pathways were accurately related to miscarriages: MAPK signaling pathway, NF-κB signaling pathway, focal adhesion, and HIF-1 signaling pathway. Activating the p38/MAPK signaling pathway inhibits trophoblast proliferation, migration, and epithelial-mesenchymal transition (EMT), resulting in miscarriage [ 37 ]. Whereas blocking MAPK/ERK1/2 signaling pathway may inhibit the growth and invasiveness of human trophoblasts [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The following KEGG pathways were accurately related to miscarriages: MAPK signaling pathway, NF-κB signaling pathway, focal adhesion, and HIF-1 signaling pathway. Activating the p38/MAPK signaling pathway inhibits trophoblast proliferation, migration, and epithelial-mesenchymal transition (EMT), resulting in miscarriage [ 37 ]. Whereas blocking MAPK/ERK1/2 signaling pathway may inhibit the growth and invasiveness of human trophoblasts [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EMT is implicated in differentiation of trophoblast cells, and immune microenvironment of maternal-fetal interface [13]. Suppression of EMT of HTR-8/Svneo has been reported to promote progression of RSA [14]. The TGF-β1induced invasion, migration, and EMT of small intestine epithelial cells were repressed by atractylenolide III [15].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, p38 MAPK can maintain pregnancy and promote labour, but its inappropriate activation can lead to adverse pregnancy outcomes 17 . Additionally, current research have shown that IL‐23 inhibits trophoblast proliferation, migration and EMT via activating p38 MAPK signalling pathway 18 . Hence, exploring the effects of miRNAs and the p38 MAPK signalling pathway is essential to study SA mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Additionally, current research have shown that IL‐23 inhibits trophoblast proliferation, migration and EMT via activating p38 MAPK signalling pathway. 18 Hence, exploring the effects of miRNAs and the p38 MAPK signalling pathway is essential to study SA mechanisms.…”
Section: Introductionmentioning
confidence: 99%